Fabrication of Polyvinyl Alcohol/Kefiran Nanofibers Membrane Using Electrospinning - Mina bagherian far; Hakimeh Ziyadi (Islamic Azad University, 2016)
The Poly (vinyl alcohol)/Kefirane nanofiber membrane was successfully fabricated for the first time using electrospinning of the polyvinyl alcohol (PVA) and Kefirane blend solution. Scanning electron microscope (SEM), attenuated total reflectance Fourier transform infrared (ATR FT-IR), and differential scanning calorimetry (DSC) were used to characterize the electrospun Poly (vinyl alcohol)/Kefirane fiber membranes. Similar analysis was done for polyvinyl alcohol nanofibers. Then, the results were compared with each other. Rheological behavior of the Poly (vinyl alcohol)/Kefirane solution was evaluated using a cone and plate rheometer. The flow curves of 6% Kefiran solution and Poly (vinyl alcohol)//Kefiran blend solution showed sufficient viscosity for electrospinning. Viscosity decreased as the shear rate has increased in two samples, with both demonstrating shears thinning behavior. Electrospinnability of Poly (vinyl alcohol)/Kefiran solution at different process conditions and Kefiran concentrations was studied. Scanning electron microscope analysis exhibited that diameter of polyvinyl alcohol nanofibers increased with increasing Kefiran. Increasing the Kefiran concentration to 6% led to the disappearance of nodes in nanofibers. Attenuated total reflectance Fourier transform infrared spectra showed that Kefiran has maintained its molecular structure during the electrospinning process. Differential scanning calorimetry of Poly (vinyl alcohol)/Kefirane nanofibers revealed lower melting point than polyvinyl alcohol nanofibers.